Effect of cell phone radiation on neutrophil of mice. (3rd August 2019) - Yinhui, Pei; Hui, Gao; Lin, Li; Xin, An; Qinyou, Tian
Abstract: Purpose: The present study aims to evaluate the effect of cell phone radiation on neutrophil of mice. Materials and methods: 40 male BALB/C mice were randomly divided into four groups as control, blank control, TD-CDMA, and LTE-advanced groups, respectively. Mice were exposed to cell phone radiation for a period of 6 weeks. Then numbers of neutrophil were detected by fully automatic hematology analyzer. Soft agar diffusion method was performed to assess the chemotaxis of neutrophils while the phagocytosis of neutrophils was determined by measuring the staphylococcus albus phagocytosis percentage. Apoptosis was analyzed by flow cytometry. Results: No significant differences were observed among the control and exposure groups regarding the numbers of neutrophils after 2 weeks' exposure to cell phone radiation, while the numbers of neutrophils in TD-SCDMA and LTE-advanced groups were seen to rise after an exposure of 4 or 6 weeks. No effect was observed on chemotaxis of neutrophils due to phone radiation. The phagocytosis of neutrophils was decreased while the apoptosis were increased both in TD-SCDMA and LTE-advanced groups after 6 weeks exposure. Conclusions: Mobile phone radiation could give rise to increase of neutrophil numbers yet with no effect whatever on neutrophils chemotaxis, and the radiation was likely to cause decrease of phagocytosis and induced apoptosis of neutrophils.